2021
DOI: 10.1111/nph.17480
|View full text |Cite
|
Sign up to set email alerts
|

Fine root production in a chronosequence of mature reforested mangroves

Abstract: Mangroves are among the world's most carbon-dense ecosystems, but have suffered extensive deforestation, prompting reforestation projects. The effects of mangrove reforestation on belowground carbon dynamics are poorly understood. In particular, we do not know how fine root production develops following mangrove reforestation, despite fine root production being a major carbon sink and an important control of mangrove soil accretion.Using minirhizotrons, we investigated fine root production and its depth variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 79 publications
2
16
0
Order By: Relevance
“…Previous local-scale studies have shown that precipitation was related to mangrove root production as in our findings (Hayes et al, 2019;, but not all (Arnaud et al, 2021).…”
Section: Global Factors Explaining the Root Productionsupporting
confidence: 54%
“…Previous local-scale studies have shown that precipitation was related to mangrove root production as in our findings (Hayes et al, 2019;, but not all (Arnaud et al, 2021).…”
Section: Global Factors Explaining the Root Productionsupporting
confidence: 54%
“…We undertook our field investigation at the Can Gio Biosphere Reserve (CGBR) in the Mekong Delta in the south of Vietnam (Figure 2). The site in CGBR is typical of many Southeast Asian mangroves, insofar as: (i) it is a dense carbon store (910.7 ± 32.2 t C ha −1 [Dung et al, 2016]); (ii) it is dominated by trees of the Rhizophora genus (Arnaud et al, 2021; Donato et al, 2011); (iii) the sediment matrix is mostly composed of clay‐sized grains (70% of sediment by weight: Arnaud et al, 2020), which is typical of deltaic or riverine mangroves (Woodroffe, 1992); and (iv) it has an average groundwater outwelling discharge of between 3.1 and 7.1 cm day −1 , which is within the range previously reported in mangroves more broadly (Taillardat et al, 2018; Tait et al, 2016). The tidal regime is irregular and semi‐diurnal, with a maximum amplitude of 3.3–4.1 m in October and November (Thi Hoa Binh et al, 2008; Van Loon et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…I G U R E 2 Location of the study area and distribution of the monitoring plots. Modified fromArnaud et al (2021) andTaillardat et al (2018) …”
mentioning
confidence: 99%
“…Belowground roots can be divided into live and dead roots, showing differences based on the mangrove species involved, sediment depth, and environmental factors (Arnaud et al 2021). Chen et al (2021) found that most live roots were concentrated in the upper 30 cm, which was called the root zone in sediment.…”
Section: Introductionmentioning
confidence: 99%
“…). In previous study in mature Vietnamese mangroves, minirhizotrons were used to investigate ne root production and the variation in root depth along a chronosequence; the researchers found that ne root production occurred deeper than 30 cm in sediment and decreased with forest age (Arnaud et al, 2021). Furthermore, ne root production and turnover rates were found to be related to sediment variables of mangroves (Xiong et al, 2017).The drivers of root decomposition contributed to the C budgets and proved that C contents from dead roots was a key source of C inputs in sediment of mangroves and saltmarshes (Ouyang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%